Extended Readings on Copyright - Sag, Matthew; Open Textbook Library (Open Textbook Library, 2019)
Extended Readings on Copyright is subject to a non-commercial Create Commons license that allows you to add, subtract, and amend as you see fit, provided you extend those terms to any derivative work based on these materials and provided your provide appropriate attribution. I encourage you to share your edits and additions with me, but it is not obligatory.Extended Readings on Copyright can be used as a stand alone textbook on United States copyright law. The individual chapters are available on this website, and these can be used to supplement other materials. Individual chapters are likely to be more up to date than the consolidated build of the book.
1. Introduction to Copyright Law -- 2. Copyright Subject Matter and Questions of Creativity, Originality, and Intellectual Creation -- 3. The Exclusion of Facts, Ideas, Functions, and Processes from Copyright Protection -- 4. The Historical Development of the Concepts of Reproduction, Adaptation, and Fair Use -- 5. The Reproduction Right -- 6. An Overview of Copyright Limitations and Exceptions -- 7. Expressive Fair Use -- 8. Fair use and non-expressive use -- 9. Copyright subject matter and the boundaries of the work -- 10. Ownership, Authorship and Transfer -- 11. Moral Rights -- 12. Formalities and Duration -- 13. Copyright and Industrial Design -- 14. Copyright in Computer Software -- 15. Distribution & First Scale -- 16. Public Performance, Display & Transmission -- 17. Secondary Liability for Copyright Infringement -- 18. Internet Safe Harbors From Claims of Copyright Infringement -- 19. Digital Rights Management and Copyright Management Information -- 20. Volitional Conduct, Linking and Ancillary Copyright -- 21. Remedies for Copyright Infringement -- 22. Procedural Issues in Copyright Litigation
In English.
Description based on online resource
Keywords: Law -- Textbooks -- United States; Property Law -- Textbooks